2022
DOI: 10.1039/d2ra01668k
|View full text |Cite
|
Sign up to set email alerts
|

Facial fabrication of few-layer functionalized graphene with sole functional group through Diels–Alder reaction by ball milling

Abstract: The widespread use of graphene as a next-generation material in various applications requires developing an environmentally friendly and efficient method for fabricating functionalized graphene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Ball milling is a simple and environmentally friendly strategy to exfoliate graphite, synthesize graphene and graphene-based materials, and pre-pare graphene oxides. Few-layer functionalized graphene with a sole functional group [124] and edge-carboxylate graphene (ECG) [125] were obtained by means of dry ball milling graphite powders with milling balls. Chandran et al [126] found that D-sorbitol could assist in the ball milling of graphite to graphene, and the polyhydric nature of D-sorbitol was able to insert and interact with layers via non-conventional OH-π and CH-π H-bonding.…”
Section: Ball-milled Graphene-based Materialsmentioning
confidence: 99%
“…Ball milling is a simple and environmentally friendly strategy to exfoliate graphite, synthesize graphene and graphene-based materials, and pre-pare graphene oxides. Few-layer functionalized graphene with a sole functional group [124] and edge-carboxylate graphene (ECG) [125] were obtained by means of dry ball milling graphite powders with milling balls. Chandran et al [126] found that D-sorbitol could assist in the ball milling of graphite to graphene, and the polyhydric nature of D-sorbitol was able to insert and interact with layers via non-conventional OH-π and CH-π H-bonding.…”
Section: Ball-milled Graphene-based Materialsmentioning
confidence: 99%